The Effect of Aldosterone on the Accumulation of Adenosine 3′:5′-Cyclic Monophosphate in Toad Bladder Epithelial Cells in Response to Vasopressin and Theophylline - Stoff, Jeffrey S. (1972)
Vasopressin and theophylline both increase the content of adenosine 3′:5′-cyclic monophosphate (cAMP) in epithelial cells of the urinary bladder of toads (Bufo marinus). Incubation of the tissue with 0.2 μM aldosterone markedly increases this response to the two agents; incubation for a similar time without steroid reduces the response. The permeability responses (sodium transport and water flow) of the intact tissue to vasopressin, theophylline, and exogenous cAMP are also considerably greater in bladders incubated with aldosterone than without. The results are interpreted as indicating that the foregoing permissive effects of aldosterone on the permeability responses to vasopressin and theophylline are mediated by a steroid-dependent increase in the accumulation of cAMP in the pertinent epithelial cells, probably as a consequence of a diminution in the rate of degradation of the intracellular nucleotide.